Changes in post-operative renal function and coagulation profile after hydroxyethyl starch administration in patients undergoing orthopedic hip surgery under spinal anesthesia - Kamal, Kirti; Bhandari, Monika; Bansal, Priyanka; Ahlawat, Geeta; Bala, Renu; Aggrawal, Diya (Asian Journal of Medical Sciences, 2021)
Background: Hydroxyethyl starch solutions which have been introduced some three decades ago, have been extensively used for treatment of intraoperative hypovolaemia. Aims and Objectives: The present prospective study was conducted to study changes in post-operative renal function and coagulation profile in patients undergoing orthopedic hip surgery under spinal anesthesia after coloading with 6% HES 130/0.4. Materials and Methods: Seventy patients, aged between 50 and 80 years, of either sex, belonging to ASA physical Status I and II, scheduled for orthopedic hip surgery under spinal anesthesia were included in the study. As per the group allocation, coloading was done with 7.5 mlkg-1 of either Group RL or 6% 130/0.4 Group HES during the 1st h of surgery. Venous samples were withdrawn before the day of surgery, on the day of surgery, and on the 3rd day of surgery. Results: No statistically significant difference between renal and coagulation profile was found among groups. Conclusion: Thus, we recommend using tetrastarch (6% HES 130/0.4) for intraoperative hypovolemia in elderly patients with normal renal function and coagulation profile undergoing orthopedic hip surgery.